Experimental inoculation of the Botox perineurally of facial nerve and followed by histological assessment for its effect on the zygomatic bone of rabbits - Ali Obayes; Sameeah Hamad; Huda Hameed (Journal of Ideas in Health, 2023)
Background: Botox, derived from the toxin produced by Clostridium botulinum, is an attenuated toxin employed as a treatment for cervical dystonia, overactive bladder, strabismus, cerebral palsy, and non-surgical cosmetic procedures. This study aimed to explore the impact of injecting Botox around the facial nerve on the left side of rabbits, specifically focusing on the histological changes in the zygomatic bone.